Measuring the task force of sexual violence prevention and response effectiveness in Jakarta State University - Siska Andrianika; Agus Priyadi; Hasbi Thaufik Oktodila; Achmad Ichsan Nusapati (Universitas Islam Malang, 2022)
The issue of the Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 30 of 2021 proves the seriousness of the government in dealing with sexual violence in universities. One form of prevention in this Ministerial Regulation is the establishment of a Task Force for the Prevention and Handling of Sexual Violence. This task force aims to be the main factor of dealing with various forms of sexual violence that can occur in universities, all includes prevention, reporting, to handling. Based on the importance of the existence of the task force, this study aims to analyze the effectiveness of establishing The Task Force of the Sexual Violence Prevention and Response in universities based on the Regulation of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia in 2021. This study uses a mixture of quantitative and qualitative methods with data samples taken from the State University of Jakarta. This research data collection technique was carried out by distributing questionnaires and conducting a literature review using the theory of effectiveness and the use of law and the concept of roles. This research found that through quantitative research, there is significant correlation between the principles of the Sexual Prevention and Response, The Task Force’s main responsibility, and the objectives of this ministrial regulation. Through qualitative research, from the organizational component and the implimentation of gender-based regulation, this ministrial regulation is proven to be an effective regulation to handling sexual violence.